Extramammary Paget's disease: A retrospective study in a medical center in Taiwan - Chia-Hsien Yen; Chih-Hung Lee; Ji-Chen Ho (Dermatologica Sinica, 2022)
Background: Extramammary Paget's disease (EMPD) is a rare malignancy occurring on apocrine sweat gland-bearing skin with occasional association with internal cancers. Its epidemiological characteristics are different between populations in Asian and Western countries. Objectives: The aim of this study was to report the clinical experience of EMPD in a single medical center in Taiwan, compare our results with previous literature, and provide strategies for diagnostic workup. Methods: Medical records and biopsies of 34 Taiwanese patients with EMPD, treated in a single medical center in Kaohsiung, Taiwan, from January 2000 to December 2019, were reviewed. The clinicopathological features, biological behavior, management, and follow-up courses of these patients were analyzed. Results: We found a male predominance in our 34 patients with EMPD, and most patients were diagnosed in their 70s. Only four patients (11.8%) had an associated malignancy while the rest had a primary cutaneous lesion. Most patients (22, 64.7%) underwent wide excision (22, 64.7%), with the rest adopting other various therapeutic modalities. The 5-year overall survival rate was 76.5%, and the statistically significant prognostic factors for survival were lymph node involvement (P < 0.001) and dermal invasion (P = 0.022). Conclusion: In summary, this single-center study described the clinical and histopathologic features of patients with EMPD in Taiwan with a review of literature. We also proposed a complete systemic workup when the diagnosis was made and an extended follow-up period as long as 5 years after the initial treatment.